2006
DOI: 10.1111/j.1365-2648.2006.03941.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurse staffing levels and hospital mortality in critical care settings: literature review and meta‐analysis

Abstract: The impact of nurse staffing levels on patients' hospital mortality in critical care settings was not evident in the reviewed studies. Methodological challenges that might have impeded correct assessment of the association include measurement problems in exposure status and confounding factors, often uncontrolled. The lack of association also indicates that hospital mortality may not be sensitive enough to detect the consequences of low nurse staffing levels in critical care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
1
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 42 publications
2
57
1
8
Order By: Relevance
“…There is evidence that nursing workload is associated with the quality of patient care and the health of workers (1)(2)(3)(4)(5) . Since the 1970s, the gold standard for nurse staffing levels in intensive care and subsequently critical care units has been one nurse for each patient (6) .…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that nursing workload is associated with the quality of patient care and the health of workers (1)(2)(3)(4)(5) . Since the 1970s, the gold standard for nurse staffing levels in intensive care and subsequently critical care units has been one nurse for each patient (6) .…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with a previous study, the increased workload in nursing was associated with the time of hospitalization of the patient (10) . This variable is clearly associated with the quality of care and the workload of the nursing staff (23)(24) , in addition to representing one of the most important indicators of morbidity of patients undergoing cardiac surgery (25) . Patients with a longer length of stay in the ICU are probably more clinically unstable and severely ill (14) , and the occurrence of complications seems to greatly contribute to time spent in the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews of studies examining nursing staffing and patient outcomes in the ICU context have shown mixed results [25][26][27]. This study seeks to extend the current literature in this area by testing the association of the NQF-endorsed nurse staffing measures on ICU outcome measures, directly matching staffing and outcome data at the unit level.…”
Section: Discussionmentioning
confidence: 99%
“…Reviews of the smaller subset of studies focused on ICU settings show similar methodological inconsistencies and inconclusive results [25][26][27]. To further knowledge on this topic, there is need for large, prospective, longitudinal, multi-center trials which use standardized nurse staffing and outcome measure definitions [18,25].…”
Section: Introductionmentioning
confidence: 99%